Model Rehabilitasi Schizoprenia Untuk Peningkatan Quality Of Life ODS - Indah Nursuprianah; Mumun Munawaroh; Risdianto Risdianto; Nuraida Absharina Awanis (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
Schizophrenia is a mental disorder that impacts cognitive functions, leading to disruptions in thinking, perception, emotion, movement, and behavior. According to the World Health Organization (WHO) data from 2013, schizophrenia is a severe mental illness that affects approximately 7‰ of the adult population, particularly within the age group of 13 to 35 years. Given the discrepancies between societal expectations and the actual handling of individuals with schizophrenia (ODS) in practice, this study aims to develop a model of schizophrenia rehabilitation to enhance the quality of life for ODS. This research employs a mixed-methods approach, incorporating the Wilcoxon test and modeling techniques. The Wilcoxon test, with a significance level of ɑ = 0.05, revealed a notable improvement in the quality of life of ODS before and after undergoing rehabilitation at the institution. The schizophrenia rehabilitation model consists of four stages: relaxation, care, rehabilitation, and day care. The final findings of this study demonstrate that the quality of life for ODS significantly improved after undergoing rehabilitation at the Gramesia Kedawung Institution in Cirebon Regency.